2018
DOI: 10.3906/vet-1803-53
|View full text |Cite
|
Sign up to set email alerts
|

The effect of using rosemary ( Rosmarinus officinalis ) in broiler nutrition on production parameters, slaughter characteristics, and gut microbiological population

Veselin PETRIČEVIĆ,
Miloš LUKIĆ,
Zdenka ŠKRBIĆ
et al.

Abstract: The aim of this study was to investigate the effects of the supplementation of different concentrations of rosemary in broiler diets from day 1 to 42 on growth performance, carcass quality, and cecal microbiological composition of chickens. The research was carried out with 1200 Ross 308 chickens, divided into 4 groups with 6 repetitions per group. The treatment groups were: control group (C) without rosemary, 0.2% rosemary group (0.2R), 0.4% rosemary group (0.4R), and 0.6% rosemary group (0.6R). Production pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…On the contrary, Kırıkçı et al (2017) stated female partridges had better carcass yield (%76.07) than male ones (%76.07) however, not significantly different, only numerically. Other studies indicated dietary rosemary supplementation didn't differ carcass weight statistically (Ghazalah and Ali, 2008;Çetin et al, 2017;El-Gogary et al, 2018;Petričević et al, 2018) In the present experiment, carcass yield was found in a range from %74.70 to 79.09, %77.07 averagely in female chukar partridges and %74.57 to %78.44, %77.02 averagely in male animals. Kokoszyński et al (2013) and Wnux et al (2014) also found no difference between male and female partridges in terms of carcass yields.…”
Section: Discussionsupporting
confidence: 52%
“…On the contrary, Kırıkçı et al (2017) stated female partridges had better carcass yield (%76.07) than male ones (%76.07) however, not significantly different, only numerically. Other studies indicated dietary rosemary supplementation didn't differ carcass weight statistically (Ghazalah and Ali, 2008;Çetin et al, 2017;El-Gogary et al, 2018;Petričević et al, 2018) In the present experiment, carcass yield was found in a range from %74.70 to 79.09, %77.07 averagely in female chukar partridges and %74.57 to %78.44, %77.02 averagely in male animals. Kokoszyński et al (2013) and Wnux et al (2014) also found no difference between male and female partridges in terms of carcass yields.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, RA restored normal growth and development in zebrafish embryos exposed to food colors (sunset yellow and crimson red) through its effect on aurora kinase A ( Swarnalatha et al, 2017 ). In addition, rosemary-supplemented feed positively impacted body weight gain, FCR, deposition of fat, and cecal microbiological composition in the broilers ( Petricevic et al, 2018 ; Farouk et al, 2022 ; Mawed et al, 2022 ). The growth-promoting effects of both phytochemicals may be attributed to the enhancement of the antioxidant activity and proliferation of the gut flora.…”
Section: Discussionmentioning
confidence: 98%
“…The growth-promoting effects of thyme have been demonstrated in broiler chickens by Hassan and Awad (2017) who reported that supplemented thyme powders (5%), in broilers diets improved growth performance and immune status (p <0.05). Petricevic et al (2018) reported that supplemented rosemary leaves powder at the level of 0.4% in broilers diets improved growth performance, fat deposition and cecal microbiological composition (p <0.05).…”
Section: Introductionmentioning
confidence: 96%